Co-encapsulation of siRNA with non-coding pDNA or Poly-L-glutamic acid in DODAB:MO (2:1) liposomes for enhanced gene silencing - Almeida, Fernando Henriques (2015)
RNA interference (RNAi) has been found to be an important biological strategy for gene silencing. This pathway can be used as a gene therapy approach by using synthetic short interfering RNA (siRNA) molecules to promote the silencing of undesirable target genes. However, the delivery of nucleic acids into the cells is a very inefficient process due to several extracellular and intracellular barriers. Several physical, chemical and biological strategies have been developed to promote the delivery of nucleic acids into cells. Although viral vectors have been reported to be the most efficient nucleic acid delivery systems, they trigger the immune system and promote high levels of toxicity. Non-viral vectors, though not as efficient as their viral counterparts, appeared as a safer method for therapeutic gene delivery. In this field, cationic liposomes emerged as one of the most promising and widely used non-viral gene carriers. Recent studies from our group have established a novel liposomal formulation for siRNA delivery, based on the cationic lipid dioctadecyldimethylammonium bromide (DODAB) and the helper lipid monoolein (MO). This liposome formulation has promoted efficient gene silencing in a human non-small cell lung carcinoma cell line (H1299). In this project, we aimed to improve the silencing efficiency of DODAB:MO (2:1) liposomes, by promoting the co-encapsulation of siRNA with additional anionic components. Poly-L-glutamic acid (PG1 or PG2) or non-coding plasmid DNA (pDNA) were added to siRNA suspension and encapsulated within DODAB:MO (2:1) liposomes. The systems obtained were compared with lipoplexes containing only siRNA. Lipoplexes were characterized in order to understand the differences caused by addition of the anionic components. The results obtained during this project suggest that the addition of either pDNA or PG molecules to siRNA/DODAB:MO lipoplexes results in systems with similar physicochemical properties, namely size and surface charge. Nevertheless, some improvements in the siRNA encapsulation efficiency, cellular internalization and cytotoxicity were obtained when compared to siRNA lipoplexes. Additionally, lipoplexes co-encapsulating siRNA and pDNA or PG have promoted higher EGFP gene silencing efficiency, suggesting that co-encapsulation of siRNA with an additional anionic cargo can improve silencing efficiency of our liposomal formulation.